Prevalence and intensity of infection and development stages of the nematode Camallanus corderoi in native fish and in the introduced trout, Oncorhynchus mykiss, in Lake Panguipulli, Chile - Gallardo, Jessica (2025)
The aim of the study was to compare the prevalence and intensity of infection and frequency of developmental stages of the nematode Camallanus corderoi in native fish (Percichthys trucha, Basilichthys australis, Odontesthes mauleanum) and in the introduced trout Oncorhynchus mykiss, as well as to compare the prevalence and intensity with capture periods, sex and size of the hosts in Lake Panguipulli in Chile. A total of 194 fish, distributed in the four species, were examined for C. corderoi in the digestive tract at the end of September (spring) of 2006 and at the end of January (summer), March (autumn) and June (winter) of 2007. Nematodes were identified after fixation in formalin-saline and diaphanization in lactophenol. Immature females and third and fourth instar larvae of C. corderoi are described for the first time in fish. Prevalence and mean intensity were higher (p<0.05) in P. trucha. Prevalence in B. australis was higher (p<0.05) and mean intensity was similar with O. mauleanum and O. mykiss. Larval stages were present in P. trucha, B. australis and O. mykiss in spring and in autumn in B. australis. Only the native fish that had a higher percentage and average of pregnant females was in P. trucha. Pregnant females were identified in spring, summer and winter in P. trucha, in summer and autumn in B. australis and in spring in O. mauleanum. Prevalence was similar between sampling periods and sex in the four hosts, as well as the mean intensity in P. trucha and B. australis (p>0.05). The number of parasites and size of P. trucha, B. australis and O. mykiss did not show significant correlation. The higher prevalence and mean intensity and higher percentage of gravid females in P. trucha suggest it as the main disseminator of C. corderoi in Lake Panguipulli.